Gastric anti-ulcer activity of leaf fractions obtained of polar extract from Wilbrandia ebracteata in mice - Coelho, R. G. [UNESP]; Gonzalez, F. G. [UNESP]; Sannomiya, M. [UNESP]; Di Stasi, L. C. [UNESP]; Vilegas, Wagner [UNESP] (Taylor & Francis Ltd, 2009)
Leaf fractions of Wilbrandia ebracteata were investigated for anti-ulcerogenic effects in ethanol and indomethacin-induced gastric ulcer assays in mice. Protective anti-ulcer effects were detected only in the ethanol-induced ulcer assay effects after pre-treatment with MeOH extract, MeOH chlorophyll-free, chlorophyll residue, HEX, DCM, aqueous MeOH fraction, ethyl acetate (EtOAc) and aqueous fractions. A potent anti-ulcerogenic effect was determined after pre-treatment of animals with EtOAc fraction, which was fractionated for isolation of active constituents. Seven flavonoids, 3',4',5,6,7,8-hexahydroxyflavonol, orientin, isoorientin, vitexin, isovitexin, luteolin, 6-methoxi-luteolin were isolated from the leaves of W. ebracteata (Cucurbitaceae) by chromatographic methods and identified by their spectral data. The data suggest that flavonoids are active anti-ulcerogenic compounds from leaves of W. ebracteata. The ability of scavenging free radicals was evaluated by DPPH reduction assay by TLC of flavonoids isolated.
Keywords: anti-ulcer activitiy; leaves; Wilbrandia ebracteata; Cucurbitaceae; C-glycosylflavones